Composição mineral e bromatológica de genótipos de palma forrageira dos gêneros Opuntia e Nopalea em diferentes estádios fenológicos - Silva, Danilo Dantas da (2019)
The cactus pear is an important forage resource for the semiarid region and widely used in animal feed. It has a great genetic diversity and there is a need to characterize the most cultivated genotypes. The objective of this study was to evaluate the variation in mineral and bromatological composition of different cladode phenological stages of cactus pear genotypes of Opuntia and Nopalea genera. To this end, collection was performed in an area implanted with genotypes at the Experimental Station of the Instituto Agronômico de Pernambuco - IPA, in Arcoverde-PE. The materials of the genus Opuntia (IPA-200016, IPA-200174, IPA-200008 and IPA-200149) and Nopalea (IPA-100004, IPA-200021 and IPA-200205) were evaluated for mineral and bromatological composition by cladodes phenological stage (young, intermediate and mature). The experimental design was completely randomized in a 7x3 factorial scheme and the obtained data were submitted to analysis of variance and the means compared by Tukey test. The content of nutrients varied N (10.55 to 13.47 g.kg-1 DM), P (3.87 to 9.12 g.kg-1 DM), K (23.18 to 34.46 g.kg-1 DM), Ca (41.72 to 81.79 g.kg-1 DM), Mg (7.03 to 7.28 g.kg-1 DM), S (2.98 to 4.16 g.kg-1 DM), B (38.64 to 80.67 mg.kg-1 DM), Fe (90.40 to 116.78 mg.kg-1 DM), Cu (2.33 to 6.65 mg.kg-1 DM), Zn (70.99 to 127.69 mg.kg-1 DM), Mn (39.84 to 317.73 mg.kg-1 DM), MS (61.42 to 83.80 g.kg-1 MN), MM (146.46 to 181,83 g.kg-1 DM), MO (818.17 to 853.54 g.kg-1 DM), EE (15.59 to 22.68 g.kg-1 DM), PB (57.51 to 71.24 g.kg-1 DM), FDN (232.57 to 357.62 g.kg-1 DM), FDA (115.61 to 213.23 g.kg-1 DM), CNF (433.12 to 504.93 g.kg-1 DM) e CHOT (738.89 a 773.56 g.kg-1 DM). The mineral and bromatological composition of cactus pear genotypes show variability in different phenological stages of cladode. Cutting at a young and intermediate phenological stage prioritizes the highest concentrations of minerals, crude protein and non-fibrous carbohydrates.